TINJAUAN YURIDIS TERHADAP PUTUSAN HAKIM DALAM PERKARA NOMOR 1.513/PID.B/2014/PN.MDN TENTANG TINDAK PIDANA PERDAGANGAN ILLEGAL SATWA LIAR YANG DILINDUNGI DIKAITKAN DENGAN PRINSIP KEADILAN - Yonggi Oktavianus; Erdianto Effendi; mexsasai indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The wildlife is all the animals that live on land, or in water, or in the air and still has the properties of wild, free-living well and are maintained by humans. In this case, the case of the crime of illegal trade in wild sata in each year has increased. It can be seen from the role of law enforcement in arresting perpetrators of illegal trade of protected wildlife is increasingly rife, especially in the city of Medan. Because now the actor has been expanding sales operations area wildlife. In this case relates to the criminal verdict against the perpetrators of such offenses, the judge's decision, especially Medan District Court judge in imposing a sentence for criminal illegal trade in wildlife must provide a deterrent effect to the defendant within the jurisdiction of the District Court of Medan. The purpose of this thesis, namely: the first verdict Judge in case number 1513 / Pid.B / 2014 / PN.Mdn already reflects the principle of fairness, the second, the demands of Attorney in case number 1513 / Pid.B / 2014 / PN.Mdn are in accordance with the principles of justice, third, Attorney reason not to take legal actions in this case. This type of research can be classified into types of normative research, because in this study the author directly by the judge's ruling in case number 1513 / Pid.B / 2014 / PN.Mdn. In the data collection techniques to examined in this study, the data sources used, the primary data, secondary data, and the data tertiary. Data collection techniques in this study with kepustakan studies, interviews and laws. From the research, there are three main issues that can be inferred. First, the Court decision in perkar number 1513 / Pid.B / 2014 / PN.Mdn very light of the prosecution. In the criminal provisions of Law No. 5 of 1990 shall be punished with imprisonment of ten (10) years and a fine of Rp. 200,000,000.00 (two hundred million rupiah). Second, the prosecutor demands in this case, the prosecutor in carrying out professional duties to the prosecutor in the prosecution of the defendant, should really look and pay attention to the evidence that has been found and has been proven in court. Third, based on the demands of the Prosecutor in the prosecution of the accused, the prosecutor should take legal actions against the criminal cases of illegal wildlife trade is protected. Suggestions author, First, in terms of implementing the authority and obligation to uphold the law, then the judge should pay more attention to the elements of a crime so that in addition to considering the aggravating and relieve the defendant. Secondly, should the prosecutor to make an appeal. So the criminal cases of illegal trade of protected wildlife, the number of cases is declining and the law enforcement agencies could save endangered animals to extinction in Indonesia, especially Medan.Keywords:Decision-Justice-Crime-Wildlife